2009
DOI: 10.3181/0805-rm-147
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Endothelial Cell Autoantigens Recognized by Anti-Dengue Virus Nonstructural Protein 1 Antibodies

Abstract: We previously showed the occurrence of autoimmune responses in dengue virus (DV) infection, which has potential implications for the pathogenesis of dengue hemorrhagic syndrome. In the present study, we have used a proteomic analysis to identify several candidate proteins on HMEC-1 endothelial cells recognized by anti-DV nonstructural protein 1 (NS1) antibodies. The target proteins, including ATP synthase beta chain, protein disulfide isomerase, vimentin, and heat shock protein 60, co-localize with anti-NS1 bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 55 publications
0
71
0
Order By: Relevance
“…Using sequence homology alignment, we found that the C-terminal region of DV NS1 protein contains cross-reactive epitopes with selfAgs (30,31). To explore the pathological role of cross-reactive epitopes in the hemorrhagic syndrome, we deleted the C-terminal region of DV NS1 protein to generate ⌬C NS1.…”
Section: Nfection With Dengue Viruses (Dv)mentioning
confidence: 99%
“…Using sequence homology alignment, we found that the C-terminal region of DV NS1 protein contains cross-reactive epitopes with selfAgs (30,31). To explore the pathological role of cross-reactive epitopes in the hemorrhagic syndrome, we deleted the C-terminal region of DV NS1 protein to generate ⌬C NS1.…”
Section: Nfection With Dengue Viruses (Dv)mentioning
confidence: 99%
“…Antibodies induced by molecular mimicry between DENV and human proteins can cross-react with platelets, coagulation factors, and endothelial cells. These autoantibodies may contribute to thrombocytopenia, abnormal coagulation and fibrinolysis, and endothelial damage in DHF/DSS patients, causing hemorrhage (16,18,32,44). However, other factors, such as proinflammatory cytokines and secreted NS1, may also contribute to the development of hemorrhage during the acute stage of DENV infection (37,(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…An additional hypothesis has been proposed, suggesting that the autoimmunity of anti-DENV antibodies contributes to the pathogenesis of DHF/DSS (14,15). Many anti-DENV antibodies that are able to cross-react with human tissues have been found (16,17). For example, anti-NS1 antibodies can bind to platelets and cause thrombocytopenia in mice (18,19).…”
mentioning
confidence: 99%
“…Given the pathological effects reported for anti-NS1 Abs, the underlying mechanisms need to be characterized and the relevant epitopes identified. Considerable progress toward these goals has been achieved (30,(65)(66)(67)(68), raising the hope that safer NS1 candidate vaccines may be developed with modified or deleted harmful epitopes such as those involved in autoimmune responses.…”
Section: Discussionmentioning
confidence: 99%